Ca2+-dependent regulation and binding of calmodulin to multiple sites of Transient Receptor Potential Melastatin 3 (TRPM3) ion channels. (July 2018) - Przibilla, Julia; Dembla, Sandeep; Rizun, Oleksandr; Lis, Annette; Jung, Martin; Oberwinkler, Johannes; Beck, Andreas; Philipp, Stephan E.
Graphical abstract: Highlights: TRPM3 channel activity is strongly reduced by increased cytoplasmic Ca 2+ concentrations. CaM binds to the full-length TRPM3 channel and to theTRPM3 N-terminus in a Ca 2+ dependent manner. The TRPM3 amino terminus comprise at least five individual calmodulin binding sites (CaMBS). Lysine residues in CaMBS2 are part of an IQ-motif and important for CaM binding and TRPM3 stability. Abstract: TRPM3 proteins assemble to Ca 2+ -permeable cation channels in the plasma membrane, which act as nociceptors of noxious heat and mediators of insulin and cytokine release. Here we show that TRPM3 channel activity is strongly dependent on intracellular Ca 2+ . Conceivably, this effect is attributed to the Ca 2+ binding protein calmodulin, which binds to TRPM3 in a Ca 2+ -dependent manner. We identified five calmodulin binding sites within the amino terminus of TRPM3, which displayed different binding affinities in dependence of Ca 2+ . Mutations of lysine residues in calmodulin binding site 2 strongly reduced calmodulin binding and TRPM3 activity indicating the importance of this domain for TRPM3-mediated Ca 2+ signaling. Our data show that TRPM3 channels are regulated by intracellular Ca 2+ and provide the basis for a mechanistic understanding of the regulation of TRPM3 by calmodulin.